Influence of the occlusal contacts in formation of Abfraction Lesions in the upper premolar - Victória Luswarghi Souza Costa; João Paulo Mendes Tribst; Alexandre Luiz Souto Borges (Brazilian Dental Science)
Objective: The aim of this study was to observe the influence of different occlusal contacts in a superior pre-molar structure using Finite Element Analysis. Material and Methods: A three-dimensional model of a superior pre-molar was designed to simulate three occlusion situations, namely central occlusion and two types of lateral occlusion contacts. The model presents enamel, dentin, a periodontal ligament and a fixation cylinder separately. All materials were considered isotropic, linear and homogeneous, and the contacts of each structure were perfectly bonded. On analysis software, a load was applied to an occlusal surface at 40° to the long axis on lateral contacts, and directed to the long axis on central occlusion contact. Results: The results were obtained in stress maps and the maximum values were then plotted in table for quantitative comparison, with the enamel concentrating more stress than dentin and the occlusal contact presenting the worst biomechanical behavior. Conclusion: Within the limitations of this study, it is possible conclude that: eccentric contacts have higher potential to develop abfraction lesions on the cervical region of teeth, thus increasing the magnitude of tensile and shear stresses.